Dead girl in 2A - Wilson, Carter (Novelist) (Sourcebooks Landmark, 2019)
"Jake Buchanan is a successful writer with an eight-year-old daughter and an imploding marriage. When he gets on a plane and discovers an instant connection with seatmate Clara Stowe, he's delighted. But when Clara confesses that she's going to Colorado to kill herself, Jake searches frantically for a way to convince her not to go through with her plan. The Dead Girl in 2A is the story of what happens to Jake and Clara after they get off that plane and the manipulative figure from their childhoods that has brought them together decades later. Intensely creepy, beautifully written, and full of Carter Wilson's signature whom-can-you-trust paranoia, this is a psychological thriller unlike any you've read before."--Publisher description.